2014
DOI: 10.1021/ml400500e
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-Arylphenyl)benzoxazole As a Novel Anti-Inflammatory Scaffold: Synthesis and Biological Evaluation

Abstract: The 2-(2-arylphenyl)benzoxazole moiety has been found to be a new and selective ligand for the enzyme cyclooxygenase-2 (COX-2). The 2-(2-arylphenyl)benzoxazoles 3a−m have been synthesized by Suzuki reaction of 2-(2-bromophenyl)benzoxazole. Further synthetic manipulation of 3f and 3i led to 3o and 3n, respectively. The compounds 3g, 3n, and 3o selectively inhibited COX-2 with selectivity index of 3n much better than that of the COX-2 selective NSAID celecoxib. The in vivo anti-inflammatory potency of 3g and 3n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(60 citation statements)
references
References 29 publications
0
59
0
1
Order By: Relevance
“…The benzoxazoles were reported to have good anti‐inflammatory activity by targeting COX‐2 isoenzyme . The, 2‐(((5‐aryl‐1,2,4‐oxadiazol‐3‐yl)methyl)this)benzo[ d ]oxazoles ( 5 a‐5 o ) reported herein in this paper was designed by scaffold hopping approach ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzoxazoles were reported to have good anti‐inflammatory activity by targeting COX‐2 isoenzyme . The, 2‐(((5‐aryl‐1,2,4‐oxadiazol‐3‐yl)methyl)this)benzo[ d ]oxazoles ( 5 a‐5 o ) reported herein in this paper was designed by scaffold hopping approach ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Shafi et al ., reported, 2‐((1‐(4‐Fluorophenyl)‐1H‐1,2,3‐triazol‐4‐yl)methylthio)benzothiazole ( IV ) selective COX‐2 inhibitor (COX‐2/COX‐1=0.44) in which benzthiazole nucleus was attached to aryl linked triazole through the methylthio (‐SCH 2 ‐) linkage . Similarly Seth et al ., reported, 2′‐benzoxazol‐2‐yl‐3‐chlorobiphenyl‐4‐ol, selective COX‐2 inhibitor (IC 50 =0.41±0.02 μM) ( V ) . Earlier our research group reported the (4‐(3‐((benzo[d]thiazol‐2‐ylthio)methyl)‐1,2,4‐oxadiazol‐5‐yl)phenyl) (morpholino)methanone ( VI ) as selective COX‐2 inhibitor (IC 50 =5.0 μM) .…”
Section: Introductionmentioning
confidence: 93%
“…Benzoxazoles are a class of heterocyclic compounds exhibiting therapeutical activities (Figure 2), such as, antifungal agents [38][39][40], cytotoxic compounds [41], as anti-inflammatory agents [42], as HIV-1 protease inhibitor [43], as an antibiotic [44], as CpIMPDH inhibitors [45], nonnucleoside HIV-1 reverse transcriptase inhibitors (NNRTI) [46], and antitumour agents [47].…”
Section: Benzoxazole Amides From Benzoylthioureasmentioning
confidence: 99%
“…[121] Recently,C hakrabortia nd co-workers synthesized some benzoxazole-based compounds that demonstratedp otentialC OX inhibition, and three of them (i.e., 95, 96,a nd 97)h avee merged as selective in vitro COX-2 inhibitors with in vivo anti-inflammatory potencyt hat is better than that of the standard anti-inflammatory drugs diclofenac and celecoxib ( Figure 39). [122] Inducible microsomal prostaglandin E 2 synthase-1 (mPGES-1), which is involvedi nC OX-2-mediated PGE2 production, has also become an ew therapeutic target of considerable interest for the treatment of inflammation and pain. [123] Compound 98 was found to be ap otent inhibitor of mPGES-1 and demonstratedg ood in vivo pharmacokinetic properties when studied in rats (Figure 40).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%